PENGARUH PENGGUNAAN E-COMMERCE SHOPEE DAN DIGITAL PAYMENT TERHADAP PERILAKU KONSUMTIF MAHASISWA - Pamungkasari, Shandra Agusti; Priono, Hero (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2025)
Introduction: This research is driven by the rapid growth of e-commerce and digital payment systems in Indonesia, especially through the Shopee platform, which is widely used by students who are considered digital natives. Students often choose online shopping because of its convenience, speed, and secure transactions. However, this ease of access can lead to overspending due to poor financial management. The purpose of this study is to determine, investigate, and demonstrate how students' consumption patterns are impacted by their use of Shopee e-commerce and digital payments. Methods: The study employs a quantitative methodology and an explanatory research design. 88 respondents make up the sample, while 713 pupils make up the population. A questionnaire was used to obtain the data. Using the measurement model (outer model) and the structural model (inner model), the analysis was conducted using Partial Least Squares (PLS) with the SmartPLS 4.0 software. Results: The results demonstrate that students' purchasing behavior is positively and significantly impacted by using Shopee e-commerce. Higher usage correlates with a stronger tendency toward impulsive buying. In contrast, digital payment usage shows a positive but not significant effect. This indicates that while digital payments may support convenience, they are not a dominant factor influencing consumptive behavior. These results imply that technology alone does not drive consumptive habits. Psychological factors, social influences, and self-control play more substantial roles. Therefore, it is recommended that financial education focusing on self-awareness, self-regulation, and social factors be promoted to help students manage their spending behavior more responsibly. Keywords: E-Commerce Shopee, Digital Payment, Consumer Behavior, Students